2016
DOI: 10.1371/journal.pone.0165891
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Long-Term Potentiation at Temporoammonic-CA1 Synapses: Potential Implications for Memory Consolidation

Abstract: Sex differences in spatial memory have long been observed in humans, non-human primates and rodents, but the underlying cellular and molecular mechanisms responsible for these differences remain obscure. In the present study we found that adolescent male rats outperformed female rats in 7 d and 28 d retention probes, but not in learning trials and immediate probes, in the Morris water maze task. Male rats also had larger long-term potentiation (LTP) at hippocampal temproammonic-CA1 (TA-CA1) synapses, which hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
36
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 74 publications
4
36
2
Order By: Relevance
“…A total of 180 transverse acute hippocampal slices (400 µm thick) from 100 adult male Wistar rats (5–7 weeks old) and 30 transverse acute hippocampal slices (400 µm thick) from three aged male mice (C57BL/6J, 16–18 months old) were used for electrophysiological experiments. We avoided using female rats and mice for our experiments primarily because hormonal alterations during the oestrous cycle can affect synaptic plasticity measurements (Monfort, Gomez‐Gimenez, Llansola, & Felipo, ; Qi et al, ; Warren, Humphreys, Juraska, & Greenough, ). Animals were housed under 12h light/12h dark conditions with food and water available ad libitum.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 180 transverse acute hippocampal slices (400 µm thick) from 100 adult male Wistar rats (5–7 weeks old) and 30 transverse acute hippocampal slices (400 µm thick) from three aged male mice (C57BL/6J, 16–18 months old) were used for electrophysiological experiments. We avoided using female rats and mice for our experiments primarily because hormonal alterations during the oestrous cycle can affect synaptic plasticity measurements (Monfort, Gomez‐Gimenez, Llansola, & Felipo, ; Qi et al, ; Warren, Humphreys, Juraska, & Greenough, ). Animals were housed under 12h light/12h dark conditions with food and water available ad libitum.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies reported overall superior spatial memory in WT male compared to female rodents (Monfort et al, 2015); others observed sex differences in search strategies, but not performance in spatial memory tasks (Locklear and Kritzer, 2014). Additional studies have reported sex differences only in spatial memory retention but not in short-term memory (Qi et al, 2016) or have found no spatial memory differences due to sex in WT young adult rodents (Frick et al, 1999;Dachtler et al, 2011). We did not observe differences in spatial memory in the Barnes maze between WT male and female 8 -12-week-old mice.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have also shown a sex-specific component in AMPAR-mediated synaptic plasticity underlying memory. Several studies have reported that differences between male and female rats in evoked AMPAR/NMDAR signaling in hippocampal synapses, along with differences in the magnitude of evoked LTP, may underlie sex differences in spatial memory (Monfort et al, 2015;Qi et al, 2016). Estrous has been shown to modulate diffusion of AMPARs to the surface in female mice (Palomero-Gallagher et al, 2003;Tada et al, 2015;Bechard et al, 2018), which may underlie part of the reported importance of estrogenic mechanisms for memory in females (Cordeira et al, 2018;Frick et al, 2018;Koss et al, 2018;Wang et al, 2018;Koebele et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In rodents, the eCB system sexual differences appear early in development (Craft et al, 2013). Sexually dimorphic regulation of synaptic plasticity or intrinsic neuronal activity in the amygdala (Bender et al, 2017; Chen et al, 2014; Fendt et al, 2013), hippocampus (Qi et al, 2016; Harte-Hargrove et al, 2015; Inoue et al, 2014; Huang and Woolley, 2012) and PFC (Li et al, 2016; Nakajima et al, 2014) have been described, but the effects of exogenous cannabinoids on synaptic plasticity in females as well as putative sex differences in its expression remain poorly explored. Our results showed that while eCB-LTD was not affected by cannabinoid exposure in pubescent and adult males, females’ eCB-LTD was ablated.…”
Section: Discussionmentioning
confidence: 99%